FRI0390 Health-Related Quality of Life in Swiss Patients with Systemic Lupus Erythematosus – A Cross-Sectional Analysis Within the Swiss Systemic Lupus Erythematosus Cohort Study (SSCS). (9th June 2015) - Chaigne, B.; Chizzolini, C.; Perneger, T.; Trendelenburg, M.; Huyun-Do, U.; Dayer, E.; Otto, P.; Stoll, T.; von Kempis, J.; Ribi, C.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that impacts on patients quality of life. Treatment in SLE not only aims to decrease disease activity and damage accrual but also to improve health-related quality of life (HRQOL). Only few studies have examined the influence of detailed disease-related organ involvement on HRQOL Objectives: To assess HRQOL and disease activity in a national Swiss multicentre cohort of patients with SLE (1;2). Methods: Cross-sectional study on patients included in the Swiss SLE Cohort Study between April 2007 and June 2014. Inclusion criteria were: age ≥18 years, SLE defined by the American College of Rheumatology (ACR) classification criteria, written informed consent, having completed a Medical Outcome Study Short Form 36 (SF-36) at baseline and assessed for SLE disease activity at the same time. HRQOL was assessed with the mental component scale (MCS) and Physical component scale (PCS) and the eight subscales of the SF-36. Disease activity was assessed by the SLE Disease Activity Index score with the Safety of Estrogens in SLE National Assessment (SELENA-SLEDAI) modification physican's global assessement score (PGA). Disease damage was assessed by the System Lupus Internation Collaborating Clinics/ACR Damage Index for SLE (SLICC). Results: Two hundred fifty-two patients were included in the study. The median [IQR] MCS was 46.5 [34.9 – 54.1] and the median [IQR] PCS of the SF-36 was 41.1 [33.2 – 47.3]. The median [IQR] SELENA-SLEDAI score was 3 [0.75 - 8]. Univariate analysis revealed significant correlations between PCS and PGA (r=-0.18, p<0.01), ESR (r=-0.24, p<0.001), hemoglobin (r=0.16, p<0.05), steroid intake (r=-0.25, p<0.0001), immunosuppressive treatment intake (r=-0.20, p<0.01), age (r=-0.23, p<0.001), body mass index (r=-0.17, p<0.05), and SLICC (r=-0.24, p<0.001), tobacco status (r=0.16, p<0.05). Significant correlations were found between MCS and PGA (r=-0.15, p<0.05), SELENA-SLEDAI (r=-0.22, p<0.0001), and ESR (r=-0.14, p<0.05). SELENA-SLEDAI inversely correlated with MCS (r=-0.22; p<0.001), role physical (RP) (r=-0.26; p<0.0001), bodily pain (BP) (r=-0.23; p<0.001), vitality (VT) (r=-0.15; p<0.05), social function (SF) (r= -0.14; p<0.05), social function (SF) (r=-0.14; p<0.05), role emotional (RE) (r=-0.28; p<0.0001), and mental health (MH) (r=-0.17; p<0.05). Musculoskeletal and renal involvements were the two dimensions of the SELENA-SLEDAI that correlate the most with SF-36 scores. SLICC inversely correlated with PCS (-0.24; p<0.001), physical functionning (PF) (r=-0.21; p<0.01), RP (r=-0.14; p<0.05), and BP (r=-0.15; p<0.05). Diabetes was the dimension of the SLICC that correlates the most with SF-36 scores. Conclusions: Health-related quality of life is low in Swiss SLE patients, particularly in those with musculoskelettal and renal involvement or diabetes. References: Ribi C. et al. Swiss Med Wkly. 2014 Chizzolini C. et al. Rev Med Suisse. 2009 Disclosure of Interest: None declared